Inhibitory effects of NaF on mitochondrial energy generation in human platelets in vitro - Tsujino, Tetsuhiro; Kasahara, Tomoni; Kawabata, Hideo; Watanabe, Taisuke; Nishiyama, Koji; Kitamura, Yutaka; Watanabe, Takao; Okudera, Hajime; Mochizuki, Tomoharu; Ushiki, Takashi; Kawase, Tomoyuki (Frontiers in Toxicology, 2024)
Backgroundfluoride is a beneficial ion that has been used in various fields, from industrial products to therapeutics. However, due to its narrow therapeutic index, fluoride sometimes acts as a toxic agent at relatively higher concentrations in the human body. Based on the interest in genetic stability, its cytotoxic effects have been investigated mainly in nucleated, adherent cells, such as fibroblasts. However, the sensitivity of blood cells, especially anucleate platelets, to fluoride is poorly understood. To fill this gap in the literature, we investigated the effects of relatively low levels of fluoride on platelet energy metabolism, function, and viability.MethodsPlatelet-rich plasma (PRP) was prepared from 15 non-smoking healthy male adults (age: 28–63) and treated with NaF (0.5 or 1.0 mM) in microtubes for up to 3 days. Platelet function was evaluated based on aggregation and adhesion activities. Platelet energy metabolism was evaluated based on intracellular ATP levels, extracellular lactate levels, and respiration activities. The mitochondrial membrane potential (Em) and localization of reactive oxygen species (ROS) were visualized using cytochemical methods. Platelet viability was evaluated by cell counting and tetrazolium reduction.ResultNaF (1 mM) significantly reduced platelet viability and inhibited functions. Behind these phenomena, NaF substantially decreased mitochondrial Em and increased ROS production along with significant decreases in oxygen consumption and ATP levels. Simultaneously, NaF increased the lactate levels. Although not statistically significant, similar effects were observed at 0.5 mM NaF.ConclusionAt relatively low levels, NaF has the potential to attenuate platelet function probably primarily through the inhibition of mitochondrial energy generation. Cytotoxicity may be directly related to ROS production. These findings suggest that when used topically, for example, for caries prevention in the oral cavity, NaF could interfere with wound healing and tissue regeneration by endogenous and exogenously added platelets in the form of PRP.